Effect of Process Parameters on the Tensile Strength of the Developed Composite of Al 6065 in Stir Casting Process - Yadav, Rajat; Dwivedi, Vijay Kumar (International Journal of Integrated Engineering, 2024)
There are numerous techniques for producing metal matrix composites (MMC) like infiltration, stir casting process, sinter-forging, diffusion bonding, etc. The stir casting process is amongst the most known techniques to synthesize MMC. In the current study, an agro-based MMC is prepared by stir casting process using waste eggshell and rice husk as primary and secondary reinforcements and Al 6065 as base material. Process parameters (PP) significantly impact the tensile strength of the finally prepared composite. The major factors also called process parameters in the stir casting process that have a determining impact on the tensile strength of hybrid MMC are temperature and the speed of stirring, duration of stirring, and temperature at which the reinforcement is allowed to be poured. The primary aim behind the current work is to evaluate the optimal values of process parameters in the friction stir casting process. 9 separate samples have been prepared at different Process Parameter for analyzing the tensile strength of the composite and these samples were machined as per the ASTM standards for performing the test of tensile strength. It was concluded that the maximum tensile strength value was found at a stirring speed of 320 rpm, the optimal stirring temperature was 630? and the time of stirring was 25 minutes. At these values of PP, the tensile strength of the prepared composite was improved by 35% in contrast to that of the base material.